A Rare Low‐Spin CoIV Bis(β‐silyldiamide) with High Thermal Stability: Steric Enforcement of a Doublet Configuration. Issue 33 (8th June 2020) - Zanders, David; Bačić, Goran; Leckie, Dominique; Odegbesan, Oluwadamilola; Rawson, Jeremy; Masuda, Jason D.; Devi, Anjana; Barry, Seán T.
Abstract: Attempted preparation of a chelated Co II β‐silylamide resulted in the unprecedented disproportionation to Co 0 and a spirocyclic cobalt(IV) bis(β‐silyldiamide): [Co[(N t Bu)2 SiMe2 ]2 ] (1 ). Compound 1 exhibited a room‐temperature magnetic moment of 1.8 B.M. and a solid‐state axial EPR spectrum diagnostic of a rare S= 1 / 2 configuration for tetrahedral Co IV . Ab initio semicanonical coupled‐cluster calculations (DLPNO‐CCSD(T)) revealed the doublet state was clearly preferred (−27 kcal mol −1 ) over higher spin configurations only for the bulky tert‐butyl‐substituted analogue. Unlike other Co IV complexes, 1 had remarkable thermal stability, and was demonstrated to form a stable self‐limiting monolayer in preliminary atomic layer deposition (ALD) surface saturation experiments. The ease of synthesis and high stability make 1 an attractive starting point to investigate otherwise inaccessible Co IV intermediates and for synthesizing new materials. Abstract : The role of spatial arrangement : Owing to ligand rigidity and spatial demand, the stabilization of a rare S = 1 / 2 spin ground state for tetracoordinate Co IV becomes possible, yielding a complex with high thermal stability and potential for applications relying on atomic layer deposition.